Long-term care facilities for the elderly: from legislation to needs - Ezequiel Vitório Lini; Marilene Rodrigues Portella; Marlene Doring; Maria Izabel Penha de Oliveira Santos (Rev Rene)
Objective: to analyze existing federal legislation on public policies that deal with the elderly’s rights, with emphasis on the assistance provided in long-term care facilities for the elderly and the practical impact of these laws. Methods: this is a documentary analysis of descriptive character. Results: one identified, among nineteen laws, decrees and ordinances in the last 25 years, significant developments aimed at the elderly’s welfare, as well as structural proposals and the supervision of long-term care institutions. Conclusion: the analysis conducted in the documents allowed the conclusion that the needs point to the decentralization of institutions, increase of vacancies and bigger financial investment of public institutions.